IMPROVING STUDENT LEARNING RESULTS THROUGH THE APPLICATION OF THE QUANTUM TEACHING MODEL - Nur Arum; Nur Fadhilah Amir (USN Kolaka, 2019)
Improving Student Mathematics Learning Outcomes through the Application of the Quantum Teaching Model. This study aims to improve the mathematics learning outcomes of students using the TANDUR type Quantum Teaching learning model with the assisted discussion method of Student Worksheets (LKS). This study is a classroom action research conducted in two cycles. The subject of this study were all students of class VIII.9 SMP Negeri 1 Marostotaling 38 students. Data sources came from students and teachers. Data collection techniques used observation, documentation and tests. The analysis technique used in this study was quantitative analysis techniques. The results showed that the application of the TANDUR type Quantum Teaching method can improve student learning outcomes. in learning Mathematics in class VIII.9 1 Public High School Maros. In addition there is an increase in student activity and teacher performance.